How do lifecycle, employment and childcare support contribute to the gender pension gap in Europe? The clustering methods analysis - Jędrzychowska, Anna; Kwiecień, Ilona; Poprawska, Ewa; Cichowicz, Ewa; Gałecka-Burdziak, Ewa (Technological and Economic Development of Economy, 2024)
Despite ongoing efforts in Europe to tackle discrimination against women in the labor market and societal roles, gender inequality remains entrenched. This study shifts focus from the design of pension systems to explore other key factors impacting women’s careers. By examining life cycle demographics, career paths, and childcare support systems, we utilize clustering to categorize European countries based on factors influencing women’s pension capital accumulation, excluding pension design. Our innovative approach highlights the significance of these factors in the gender pension gap. Findings suggest demographic and social similarities across countries do not necessarily equate to equitable retirement scenarios for women compared to men, underscoring the potential of pension system design to mitigate disparities. Using Ward’s method and the silhouette index for country classification on 10 variables, our analysis reveals distinct differences in gender pension gaps across Southern, Northern, Western, and Eastern Europe. This divergence, alongside observed differences in retirement outcomes for women affected by prior pension regulations, points to increasing challenges for younger European women in achieving pension parity with past generations. First published online 10 October 2024